PENGARUH PENDEKATAN ETNOPEDAGOGI DAN KARAKTER INTEGRITAS TERHADAP KEMAMPUAN LITERASI BUDAYA SISWA SEKOLAH DASAR - Claudia Marpaung; Syarifah; Hidayat (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
The aim of the research is to determine the influence of the ethnopedagogical approach and the character of integrity on the cultural literacy abilities of elementary school students. This research aims to analyze: (1) the influence of the ethnopedagogical approach on students' cultural literacy abilities. (2) the influence of the character of integrity on students' cultural literacy (3) the interaction between the ethnopedagogical approach and the character of integrity on students' cultural literacy abilities. This research was conducted on class IV students at SDN 107416 Sugiharjo and SDN 101865 Bintang Meriah with a total of 90 students. This research is of the Quasi Experimental Design type. Data analysis was carried out using SPSS 22.0 with 2x2 factorial. The instruments used were an integrity character questionnaire and a cultural literacy skills test. The research results show: (1) There is an influence of the ethnopedagogical approach on students' cultural literacy abilities with (=2.068) so that Ha is accepted and H0 is rejected; (2) There is an influence of integrity abilities on students' cultural literacy abilities with (=68,500) so that Ha is accepted and H0 is rejected; (3) There is an interaction between the ethnopedagogical approach and the character of integrity on students' cultural literacy abilities with (=27,875). Keywords: Ethnopedagogical Approach, Integrity Character, Literacy Ability